2012
DOI: 10.1007/s10764-012-9588-1
|View full text |Cite
|
Sign up to set email alerts
|

Risky Business? Lethal Attack by a Jaguar Sheds Light on the Costs of Predator Mobbing for Capuchins (Cebus capucinus)

Abstract: While some primates attempt to avoid predation by fleeing or hiding, others actually approach, harass, and sometimes attack potential predators, a behavior known as mobbing. Mobbing seems to invite obvious risks, but predators have rarely been observed to injure or kill animals that harass them. The true costs of predator mobbing and the functional significance of this behavior remain poorly understood. Here, we report a fatal attack by a jaguar (Panthera onca) on a mobbing capuchin (Cebus capucinus) that we o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
(33 reference statements)
1
10
0
1
Order By: Relevance
“…In a review of the interactions between baboons and their predators, Cowlishaw [1994] reports 1 case in which mobbing proved fatal for the baboon involved. My colleagues and I have reported a fatal attack by a jaguar on a mobbing capuchin monkey [Tórrez et al, 2012], and observers have also reported a case in which an infant tamarin monkey died as a result of a bite it sustained while mobbing a venomous snake [Correa and Coutinho, 1997]. These lethal attacks demonstrate that mobbing can be extremely costly.…”
Section: You Only Die Once: Evaluating the Costs Of Predator Mobbingmentioning
confidence: 98%
See 1 more Smart Citation
“…In a review of the interactions between baboons and their predators, Cowlishaw [1994] reports 1 case in which mobbing proved fatal for the baboon involved. My colleagues and I have reported a fatal attack by a jaguar on a mobbing capuchin monkey [Tórrez et al, 2012], and observers have also reported a case in which an infant tamarin monkey died as a result of a bite it sustained while mobbing a venomous snake [Correa and Coutinho, 1997]. These lethal attacks demonstrate that mobbing can be extremely costly.…”
Section: You Only Die Once: Evaluating the Costs Of Predator Mobbingmentioning
confidence: 98%
“…These attacks are impressive both in their intensity and in the seemingly large risks that participants take in approaching, pestering and sometimes physically assaulting predators as large as leopards and jaguars [Cowlishaw, 1994;Lloyd et al, 2006;Tórrez et al, 2012]. The cooperative nature of the attacks is also intriguing: despite the apparent danger, group mates often rush to join the mob surrounding a potential predator and frequently threaten it in a highly coordinated fashion.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed behavioral responses of groups to the two types of predator models also suggest escape specificity based on pred- Mobbing is a risky behavior for these small primates (e.g., Tórrez, Robles, González, & Crofoot, 2012) and may function more as a deterrent to ambush predators than pursuit predators (Crofoot, 2012). Finally, although sakis called at both model types, they produced loud vocalizations at a continuous rate to the jaguar models, whereas they produced high-pitched, whistle-like calls in brief bursts to the harpy models.…”
Section: Do Saki Monkeys Have Predator-specific Responses In Both Pmentioning
confidence: 99%
“…Potential predators of primates include felids, canids, mustelids, snakes, crocodiles, raptors and other primates [Isbell, 1994;Mil ler and Treves, 2007]. Predation on primates is rarely observed [Matsuda and Izawa, 2008;Barnett et al, 2011;Tórrez et al, 2012], but, as Ferrari [2009] has pointed out, this may merely indicate how very effective primate vigilance and antipredator behaviours can be [Asensio and Gómez-Martín, 2002;Miranda et al, 2006;Mourthé, 2011].…”
Section: Introductionmentioning
confidence: 99%